Larangan Menikah pada Bulan Muharram pada Masyarakat Suku Jawa di Desa Pantai Cermin - Sri Nurmaya; Muhammad Saleh (Peduli Riset dan Pengabdian Masyarakat, 2024)
The prohibition on marriage during the month of Muharram is a tradition that still persists in the Javanese community of Pantai Cermin Village. This research aims to reveal the meaning, practice and transformation of this tradition in the context of dynamic socio-cultural change. Through a qualitative approach that combines in-depth interview methods, participant observation, and document study, this research seeks to understand how this tradition is constructed, maintained, and transformed by society. The results of the research show that the prohibition on marriage during the month of Muharram has strong historical roots related to beliefs. Javanese animism and cosmology. This tradition is believed to have symbolic meaning related to the cycle of life, fertility and fate. Apart from that, this prohibition also functions as a social control mechanism, maintaining politeness values, and strengthening group identity. However, in the context of modernization, this tradition has experienced a shift in meaning and practice. The younger generation tends to be more open to change and is starting to question the rationality of the ban. Factors such as education, urbanization, and the influence of mass media also influence people's attitudes towards this tradition. This research highlights the importance of understanding the dynamics between tradition and modernity in the context of rural community life. Tradition is not something static, but a social construction that continues to change along with changing times. The prohibition on marriage during the month of Muharram is a concrete example of how traditions can survive and change at the same time. The results of this research have implications for efforts to preserve culture, develop policies that are sensitive to diversity, and a deeper understanding of the socio-cultural dynamics of society.